Isoflavones Promote Mitochondrial Biogenesis - Rasbach, Kyle A.; Schnellmann, Rick G. (The Journal of pharmacology and experimental therapeutics, 2008)
Mitochondrial damage is often both the cause and outcome of cell injury resulting from a variety of toxic insults, hypoxia, or trauma. Increasing mitochondrial biogenesis after renal proximal tubular cell (RPTC) injury accelerated the recovery of mitochondrial and cellular functions (Biochem Biophys Res Commun355: 734–739, 2007). However, few pharmacological agents are known to increase mitochondrial biogenesis. We report that daidzein, genistein, biochanin A, formononetin, 3-(2′,4′-dichlorophenyl)-7-hydroxy-4 H-chromen-4-one (DCHC), 7-hydroxy-4 H-chromen-4-one (7-C), 4′7-dimethoxyisoflavone (4′,7-D), and 5,7,4′-trimethoxyisoflavone (5,7,4′-T) increased peroxisome proliferator-activated receptor γ coactivator (PGC)-1α expression and resulted in mitochondrial biogenesis as indicated by increased expression of ATP synthase β and ND6, and 1.5-fold increases in respiration and ATP in RPTC. Inhibition of estrogen receptors with ICI182780 (fulvestrant) had no effect on daidzein-induced mitochondrial biogenesis. The isoflavone derivatives showed differential effects on the activation and expression of sirtuin (SIRT)1, a deacetylase and activator of PGC-1α. Daidzein and formononetin induced the expression of SIRT1 in RPTC and the activation of recombinant SIRT1, whereas DCHC and 7-C only induced the activation of recombinant SIRT1. In contrast, genistein, biochanin A, 4′,7-D, and 5,7,4′-T only increased SIRT1 expression in RPTC. We have identified a series of substituted isoflavones that produce mitochondrial biogenesis through PGC1α and increased SIRT1 activity and/or expression, independently of the estrogen receptor. Furthermore, different structural components are responsible for the activities of isoflavones: the hydroxyl group at position 7 is required SIRT1 activation, a hydroxyl group at position 5 blocks SIRT1 activation, and the loss of the phenyl ring at position 3 or the 4′-hydroxy or -methoxy substituent blocks increased SIRT1 expression.